DEVELOPMENT OF ELECTRONIC SERVICES FOR LICENSING MANAGEMENT (ESPESI) - setuju setuju (VANOS Journal of Mechanical Engineering Education, 2019)
Research and Development 4-D research design. Phase 4-D includes: define, design, develop and disseminate. The define phase aims to gather various information related to the product to be developed. The design phase aims to prepare the initial product design. The develop phase aims to produce a decent website. Disseminate phase is the final stage in product development. The subjects in this study consisted of two namely validator (expert expert online administration system and administration). The results of research on the development of eSpeSI according to validation or assessment from experts in the appropriate or good category if it will be applied in the field with the page https://ptm.ustjogja.ac.id/spesi/web/, while based on trials from users in this case students UST mechanical engineering education by stating the response was very good.